Super science experiments ebook Build it: build rockets and racers and test energy forces!. - Harris, Elizabeth Snoke (Super Science., 2020)
With more than 80 fun experiments, SUPER Science Experiments: Build It is the ultimate lab book for kids who want to build cool stuff! This fact- and fun-filled book includes tons of simple, kid-tested science experiments, many of which can be done with items from around the house, and require little to no supervision! That's right— no adult help needed. That means no grown-ups doing all the fun stuff while you watch. You can do lots of messy, cool, mind-blowing experiments all by yourself! All the supplies you need are probably already in your home. No fancy gadgets or doohickeys needed! Whether you want to build your own catapult, lava lamp, rocket, or even a light bulb, this book has something for everyone. Each experiment features safety precautions, materials needed, step-by-step instructions with illustrations, fun facts, and further explorations. With SUPER Science Experiments: Build It, kid scientists like you can: Make a chair with newspapers Erupt a ketchup volcano Send a rocket into the air with the stomp of your foot See which direction you're facing with a homemade compass Race little cars made from toilet paper tubes Build an electromagnetic motor And complete many other SUPER science experiments! At once engaging, encouraging, and inspiring, the SUPER Science Experiments series provides budding scientists with go-to, hands-on guides for learning the fundamentals of science and exploring the fascinating world around them. Also in this series, check out: Cool Creations, At Home, and Outdoor Fun. There's no better boredom-buster than a science experiment. You will learn something and astound and amaze your friends and family. So, what are you waiting for? Get experimenting!